Students Perspective Towards Writing Descriptive Text On Instagram Post - Widi Syahtia Pane; Jordy Anggara Kristian (Borneo Educational Journal (Borju), 2022)
Using "Instagram" as a learning medium is an easy way to help students learn descriptive text. This research is limited on perspective of students in writing descriptive text on instagram. The research is applied to one class of XI IPA1 with the number of students as many as 7 students in SMA Negeri 1 Linggang Bigung, Kutai Barat. from the result of pre research from XI IPA 1 there is 7 students who makes a descriptive text caption on Instagram post. In this research the researchers employ a qualitative approach in this research qualitative data collecting in this research. The research instrument is an interview (in-depth interview). The theory triangulation technique is carried out in testing the validity of the data using more than one perspective in discussing the problem research, so that they can be analyzed and more complete can be drawn comprehensive conclusions. Keywords: students perspective, writing, descriptive text, Instagram, caption